2009
DOI: 10.2116/analsci.25.21
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Studies on the Development of High-Performance Liquid Chromatographic Methods with Fluorescence or Chemiluminescence Detections and Their Practical Applications

Abstract: This review describes a comprehensive investigation focusing on syntheses of analytical reagents, followed by their utilization in development of analytical methods, and leading to practical applications for rational use of medicaments centering on abused drugs. Many kinds of analytical reagents for fluorescence and chemiluminescence detections have been synthesized with the intention of improving sensitivity. By properly combining the developed analytical reagents with an HPLC separation technique, one could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…3,4 The Centers for Disease Control and Prevention (CDC) in the United States found that drug abuse increased by 23% between 2010 and 2014. In 2014, the death toll was more than 47000.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The Centers for Disease Control and Prevention (CDC) in the United States found that drug abuse increased by 23% between 2010 and 2014. In 2014, the death toll was more than 47000.…”
Section: Introductionmentioning
confidence: 99%
“…A practical and accurate analysis method is a primary step in the rational use of pharmaceuticals. 16 Therefore, a dissolution method to tablets of rifaximin has been developed and validated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Tel./Fax: +81-95-819-2450; E-mail: naka-ken@nagasaki-u.ac.jp sitive HPLC-FL and -CL methods of biologically interesting compounds including bioactive components and drugs of abuse (e.g., stimulants, narcotics and anorectics) in various matrices such as urine, plasma and hair using FL labels such as 4-(4,5-diphenyl-1H-imidazol-2-yl)benzoyl chloride (DIB-Cl) and 4-(N,N-dimethylaminosulphonyl)-7-fluoro-2,1,3-benzoxadiazole (DBD-F). 1) Representative FL labeling reagents and target compounds discussed in this review are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%